The Role of Artificial Intelligence in Promoting Bharatiya Bhashas in the Digital Age - Shakuntala A. Mengani, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
In the digital age, Artificial Intelligence (AI) has emerged as a powerful catalyst in preserving, promoting, and revitalizing Bharatiya Bhashas (Indian languages), which embody India’s rich cultural, literary, and civilizational heritage. AI-driven technologies such as Natural Language Processing (NLP), Machine Translation, Speech Recognition, Text-to-Speech systems, and Optical Character Recognition (OCR) have significantly enhanced the digital presence and accessibility of Indian languages across platforms. These tools enable real-time translation, voice-based interfaces, and multilingual content creation, thereby bridging the digital divide between English and non-English speakers.AI also plays a crucial role in language preservation by digitizing classical manuscripts, folk literature, and oral traditions, ensuring their transmission to future generations. Government initiatives like Bhashini and Digital India leverage AI to promote inclusive governance by facilitating citizen-centric services in regional languages. Furthermore, AI-powered educational technologies support personalized learning in mother tongues, improving literacy and learning outcomes.Despite challenges such as data scarcity, linguistic diversity, and script complexity, continuous advancements in AI research and collaborative efforts between the state, academia, and industry are strengthening the digital ecosystem for Bharatiya Bhashas. Thus, AI not only democratizes digital access but also reinforces linguistic diversity, cultural identity, and inclusive development in contemporary India.
Keywords: Artificial Intelligence; Bharatiya Bhasha; Indian Languages; Language Preservation; Digital Inclusion; Translation Technology